Música no 1º ano do ensino fundamental: uma proposta de vivência musical para uma escola regular - Machado, Marta Caroline (2014)
This paper resulted from a Research-Action through a proposal of a musical experience in the 1º year of a primary education in a regular school in Goiania; it adopts music as a subject in the curricular grade aiming to propitiate to the student the integral development and a musical apprenticeship in particular. The participants in the search were individuals between six (06) and seven (07) years old, officially enrolled in a public school that obeying the Law 11.769/2008 makes feasible the contact from the individual with the music, as a subject foreseen in the curriculum. The effort realized with these students had as a theoretical base the studies of musical educators and theorists of education. The accomplished search in the teaching institution took the individuals to a musical experience through sections/lessons of 50 minutes, once a week, that involved activities of practical/playful explanations. The data were collected through protocols and filming. The filming resulted in analysis made by a jury of 3 music teachers/researchers, chosen accordingly to their acting in the focused area of the musical education. The entirety of the data were part of the final analyses, considered the results of the appraised by the jury, the planning of the sessions/lessons and the respective protocols pertinent to the observations made by the researcher. This data, composed under the theoretical argumentation by Jean Piaget (1976, 2013), Kodaly, Dalcroze and Orff (2011); and under the musical educators of the Psychology of Music, Leão (2009) and Ilari (2010) discussed the appearance of the following aspects, considered as criterion of evaluation: 1 – cognitive; 2 – affective; 3 – psychomotor; 4 – intellectual; 5 – hability; 6 - interpersonal; 7 – attitude; and how the execution of these substantiated aspects might have guided to the musical apprenticeship of the individuals. The oriented aspects were relevant in the analysis of the data whereas it was observed that occurred changes in the behavior and in the apprenticeship of the students who participated in the research during the period of six (06) months. In the beginning of the musical experience there was a novice class that exposed themselves only to the music in an informal manner and that inside of the school they had the possibility to learn much more besides what to sing. The class experienced a new form of expressing new forms of looking at music, experiencing its essential elements. Also, the class demonstrated to possess different attitude and behavior toward each situation, adding body movement based on the practice of the rhythmic and sonority, to musically develop and to be more participatory-creative from the proposal to experience music in the classroom. The results leaded to a conclusion that the proposal of this strategic model for the teaching of “Music in the 1º year of Basic Education” (that deals with a proposal of a musical experience for a regular school) was significant and is available to be commented in the academic sphere and known in the practice of the regular teaching in the schools.